A BIBLIOMETRIC ANALYSIS: MARKET SUSTAINABILITY FOR SECOND-HAND PRODUCTS - Ai Ling Lim; Carolina Sandra Giang, (Malaysian Journal of Business and Economics (MJBE), 2023)
The rising global trend towards sustainable consumption has generated substantial interest in second-hand goods as a potential substitute for traditional purchases. Consequently, this study offers an in-depth bibliometric and literature review examination of academic research on second-hand commodities. The content explored herein is deemed to make a significant scholarly contribution to this area of study. A total of 401 eligible articles, authored between 1974 and 2022, were discovered using the appropriate keywords second-hand, pre-loved, or pre-owned. The bibliometric study reveals a consistent rise in the volume of academic articles concerning second-hand goods since 2019. Notably, the leading institutions producing this literature include Cebu Technological University, the University of Tehran, and the University of Hong Kong. Furthermore, the research uncovered five main subject areas: vintage and nostalgia, sustainability, circular economy, fashion, and sharing economy. Most studies of second-hand products focus on how design can enhance environmental performance. One of the five co-words analysis clusters scrutinises sustainable design users' behavior. This can help scholars in related fields select research partners and directions.